2007
DOI: 10.1016/j.jcrs.2007.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal ring segment implantation for the management of keratoconus: Safety and efficacy

Abstract: Intacs implantation appeared to be effective in improving UCVA and BSCVA in patients with mild to moderate keratoconus and contact-lens intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
9
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 27 publications
8
135
9
5
Order By: Relevance
“…[19][20][21] Most of the published studies analyzing the effectiveness of ICRS implantation for the treatment of keratoconus agree that there is a significant flattening of the central cornea after the procedure. [4][5][6][7][8][22][23][24][25] Our results confirm that finding, as we found a statistically significant reduction in the keratometry readings in all grades of keratoconus. We observed that the largest reduction in mean keratometry was found in those cases with the most severe disease.…”
Section: In This Study We Evaluated the Outcomes Of Icrssupporting
confidence: 91%
See 1 more Smart Citation
“…[19][20][21] Most of the published studies analyzing the effectiveness of ICRS implantation for the treatment of keratoconus agree that there is a significant flattening of the central cornea after the procedure. [4][5][6][7][8][22][23][24][25] Our results confirm that finding, as we found a statistically significant reduction in the keratometry readings in all grades of keratoconus. We observed that the largest reduction in mean keratometry was found in those cases with the most severe disease.…”
Section: In This Study We Evaluated the Outcomes Of Icrssupporting
confidence: 91%
“…There are several publications in the literature showing that ICRS implantation in keratoconus eyes results in an improvement of the CDVA. 4,5,8,11,[20][21][22][23][24]29 However, in the present study, patients with the milder form of the disease (patients classified as grade I) showed a statistically significant decrease in the CDVA. This might be related to the fact that in those investigations, the analysis of the outcomes regarding CDVA was performed evaluating all the population under study as a whole, without considering the degree of visual impairment.…”
Section: In This Study We Evaluated the Outcomes Of Icrscontrasting
confidence: 78%
“…So, in good cases an important flattening in the central cornea was confirmed as described by others. [8][9][10][11][12][24][25][26][27][28] Instead, for group B only K 2 had a significant decrease.…”
Section: Discussionmentioning
confidence: 91%
“…27,30 Bazı cerrahlar ise implantasyon kolaylığı açısından dik aksa bakmaksızın insizyonun temporal bölgeden yapıl-masını önermektedirler. 31,32 İnsizyon bölgesinin sonuçlar üzerindeki etkisini karşılaştırmalı olarak değerlendiren çalışma mevcut değildir. Benzer şe-kilde tünel genişliği hakkında da görüş birliği mevcut değildir.…”
Section: Cerrahi̇ Planlamaunclassified
“…Amsler-Krumeich keratokonus sınıflamasına göre; sonuçlar evre 1 ve 2'de evre 3'e göre daha iyidir. 31,45 Evre 4'te ise segment implantasyonunun faydası çok sınırlıdır, hatta bazı yayınlara göre görme kaybına yol açmaktadır. 46 Progresyonu durmuş hastalıkta yaşın sonuçlar üzerindeki etkisi minimaldir.…”
Section: Sonuçlarunclassified